Evaluasi Penerimaan Bea Perolehan Hak Atas Tanah Dan Bangunan (BPHTB) Di Kabupaten Bekasi Tahun 2020-2021 - Nimas Saputri; Ratih Kumala (Jurnal Ilmu Administrasi Publik, 2022)
BPHTB (Fees for Acquisition of Land and Building Rights) is a tax that must be paid by those who carry out rights transfer transactions directed to BPHTB taxes, including buying and selling, grants, inheritance, exchange, etc. As is known in 2020- 2021 the whole world, including Indonesia itself, was hit by the Covid-19 pandemic. At that time, the BPHTB collection in Indonesia was always over target. The purpose of this study was to determine the evaluation of BPHTB collection at the Regional Revenue Agency (Bapenda) of Bekasi Regency in 2020-2021. The research was conducted at the Bapenda of Bekasi Regency using qualitative methods to find out what kind of programs and systems they are running. The data was obtained from interviews with several sources. The results of this study indicate that the evaluation of the collection of Fees for Acquisition of Land and Building Rights in Bekasi Regency in 2020-2021 was implemented properly, where the collection of BPHTB was in accordance with applicable procedures, and during the Covid-19 pandemic this was done online. The local government should try to reduce the market price or transaction value and increase the Acquired Value of Non- Taxable Tax Objects (NPOPTKP) from Rp.60,000,000 to Rp.80,000,000. BPHTB revenue in 2020 exceeded the target, which was Rp.954,288,497,549 or 127% of the revenue target of   Rp.750,000,000,000,000.   Meanwhile,   in   2021   BPHTB revenue in Bekasi Regency was only able to be realized in the amount of Rp. 909,108,452,353 or 99% of the specified target of Rp. 915,000,000,000. The obstacles that arose were limited operating hours, BPHTB validation, difficulties in determining transaction values, and delays in property activities. Efforts that should be made are to implement health protocols, apply online BPHTB validation, provide counseling, and reactivate property activities.